Hubs, influencers, and communities of executive functions: a task-based fMRI graph analysis - Davis, Alexandra T. (Frontiers in Human Neuroscience, 2025)
IntroductionThis study investigates four subdomains of executive functioning—initiation, cognitive inhibition, mental shifting, and working memory—using task-based functional magnetic resonance imaging (fMRI) data and graph analysis.MethodsWe used healthy adults’ functional magnetic resonance imaging (fMRI) data to construct brain connectomes and network graphs for each task and analyzed global and node-level graph metrics.ResultsThe bilateral precuneus and right medial prefrontal cortex emerged as pivotal hubs and influencers, emphasizing their crucial regulatory role in all four subdomains of executive function. Furthermore, distinct hubs and influencers were identified in cognitive inhibition and mental shifting tasks, elucidating unique network dynamics. Our results suggest a decentralized brain organization with critical hub regions pertinent to conditions such as stroke and traumatic brain injury.DiscussionThe precuneus and medial prefrontal cortex stand out as consistent, domain-general nodes in our findings, which show both unique and shared neural hubs across executive function subdomains. The presence of distinct hubs in cognitive inhibition and mental shifting tasks suggests flexible, task-specific network configurations. A decentralized yet structured brain network may also promote cognitive resilience.